A resolução de problemas como estratégia de integração entre o rigor matemático e suas aplicações no ensino médio - Santos, Thaís Melo dos (2022)
The research aimed to analyze the problem solving as a strategy to establish the relation between mathematical rigor and its applications in high school. The analysis was conducted through the bibliographic survey of theoretical references that brought theoretical support for the research, through their studies, such as D'Ambrósio (1997), Moreira (2002), Polya (1985) and the field research from the interpretation of the conceptions of three high school mathematics teachers, from the school public network of the state of Amazonas, in the city of Manaus. With the qualitative approach, there is the methodological path, using Cresswell (2010) and Flick (2009) studies. For this, it was applied the technique of data collection, the semi-structured interview, based on Lüdke and André (1986), made by Google Meet, through Bardin (2006) analysis. In general, the research results indicate that problem solving exceeds the relations of a concept with an application, it refers to a learning from practical situations of the students' experiences, which can awaken their interest and develop their skills and competences. Thus, we highlight the importance of using contextualized situations for the relation between concept-application, so that students can notice mathematics and its role in their daily lives. As a proposal, we suggest the use of ENEM as a resource to be explored by teachers and students, due to the presence of contextualized questions in this exam, which allows students to understand mathematical concepts and their usefulness. Keywords: Application. Mathematical Concepts. Problem Solving. Mathematical Rigor.